Lemon Juice as a Natural Biodegradable Catalyst for an Ecofriendly One-Pot Pseudo-Three-Component Synthesis of N,1-Dimethyl-6-(methylsulfanyl)-3,5-dinitro-1,4-dihydropyridine-2-amines - Saigal, Saigal; Sunny, Steeva; Seth, Kapileswar (Synlett, 2025)
A one-pot pseudo-three-component reaction strategy has been designed for synthesizing all-carbon-functionalized hexasubstituted N,1-dimethyl-6-(methylsulfanyl)-3,5-dinitro-1,4-dihydropyridine-2-amines under neat conditions using inexpensive, readily available, natural, biodegradable lemon juice as a catalyst. The acidic reaction environment induced by lemon juice provided a superior catalytic performance, with a high reaction rate and high product yields, to those of a pool of Lewis and Brønsted acid catalysts. The wide substrate scope and functional-group tolerance permitted diversity creation with electronic and structural variations in a robust and operationally simple manner. The recoverability/reusability of the lemon juice catalyst and the easy purification of the end products by precipitation/filtration avoid the need for column chromatography or hazardous organic solvents and confirm that this is an environmentally benign sustainable technology. Moreover, a gram-scale operation and chemical modifications of the final products demonstrated some promising advantages.
Keywords: 1,4-dihydropyridines; acid catalyst; solvent-free reaction; green chemistry; lemon juice